Sintering kinetics and mechanism of vitreous nanoparticles - Kirchhof, Martin; Förster, Henning; Schmid, Hans-Joachim; Peukert, Wolfgang (Journal of Aerosol Science, 2012)
The sintering of vitreous nanoparticle doublets is investigated numerically by a volume of fluid method coupled to Hamaker summation and experimentally by a high-temperature sintering flow reactor as well as by doublet shape analysis in the transmission electron microscope. In particular, the characteristic differences between nanoparticulate and bulk sintering are studied. The sintering mechanism of vitreous nanoparticles is determined to be viscous flow with interparticle van der Waals interactions acting as additional driving force. The early stages of the nanoparticle sintering kinetics are inversely proportional to the square of the particle size, instead of an indirect proportionality to the first order of the particle size for the entire bulk process. The transition between nanoparticulate and bulk sintering is localised to primary particle diameters of approx. 200-300nm. © 2011 Elsevier Ltd.
Keywords: Nanoparticles; Silica; Sintering; Van Der Waals interactions; Viscous flow